LD pumped quasi-three-level 928 nm laser with Nd:Gd0.69Y0.3TaO4 mixed crystal. (April 2019) - Yao, Wenming; Yan, Renpeng; Wu, Wentao; Li, Kang; Yu, Xin; Ma, Yufei; Peng, Fang; Zhang, Qingli; Dou, Renqin; Copner, Nigel; Gao, Jing
Highlights: 4 F3/2 → 4 I9/2 laser transition at 928 nm in a Nd:GYTO mixed crystal is realized. A comparative study of emission was performed under the pump at 808 nm and 879 nm. Improved performances were achieved under direct pumping into the emitting level. Abstract: We report on a 928 nm laser based on quasi-three-level transition of 4 F3/2 → 4 I9/2 in a Nd:Gd0.69 Y0.3 TaO4 mixed single crystal. With LD pumping at 808 nm, an output energy of 29.8 mJ at 928 nm is achieved with an optical-to-optical efficiency of 16.5% and a slope efficiency of 21.2%. In comparison, using 879 nm LD pumping, the maximum output energy at 928 nm reaches 48.5 mJ with an optical-to-optical efficiency of 33.4% and a slope efficiency of 38.0%.